A saúde pública e saneamento básico: análise dos avanços, desafios e perspectivas da qualidade de vida da população residente no município de Santarém, Brasil - FERNANDES, Alejandro Pereira (Universidade Federal do Oeste do Pará, 2025)
This dissertation analyzed public health and basic sanitation, focusing on their effects on quality of life and basic sanitation policies in the municipality of Santarém, in the state of Pará. Within the context of the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 6 (Clean Water and Sanitation), the research sought to understand how sanitation infrastructure impacted the quality of life of the local population. The methodology adopted was exploratory and descriptive, with a qualitative approach, developed in three phases. Initially, a systematic literature review was conducted using databases such as Web of Science, SciELO, and Scopus, with the descriptors "Basic sanitation AND Public health AND Quality of life AND Environmental health AND Water pollution." Subsequently, field data were collected through visits to critical areas of the city and sewage treatment plants, as well as analysis of data provided by the municipal government. Finally, the data were analyzed and compared with existing literature, supporting the development of this dissertation and scientific articles. The results, based on statistical data, public data, and research in the field, indicated that the fragility of the sanitation infrastructure contributed significantly to the incidence of diseases such as amoebiasis, diarrhea, Hepatitis A, and arboviruses, in addition to contributing to environmental degradation and the deepening of social inequalities. Based on the literature, the research also highlighted water contamination by fecal coliforms, the presence of Escherichia coli, total phosphorus pollution, and bacterial resistance in aquatic environments, compromising public health. It was also found that the precariousness of basic sanitation was exacerbated by disorderly urban growth, the lack of sewage treatment, and inadequate solid waste disposal. Thus, the data indicated that, despite the existence of an advanced legal framework, the effective implementation of sanitation policies in Santarém faced significant limitations. Rapid urbanization, lack of oversight, and low coverage rates of basic services have revealed the urgent need for more effective planning and integrated actions between public authorities, civil society, and research institutions to improve public health and quality of life policies.
Keywords: Poluição hídrica; Qualidade de vida; Saneamento básico; Saúde pública; Saúde ambiental; CNPQ::CIÊNCIAS SOCIAIS APLICADAS